Outcomes of adenoidectomy with and without tonsillectomy in patients younger than 2 years with moderate to severe upper airway obstruction. (October 2021) - Taniguchi, Kenshiro; Yoshitomi, Ai; Kanemaru, Asako; Baba, Shintaro
Abstract: Objectives: The effectiveness of adenotonsillectomy for obstructive sleep disorder breathing (OSDB) in children under age 2 years is unclear. The present study aimed to identify the perioperative symptoms and clinical outcomes of adenoidectomy and tonsillectomy in very young children. Patients and methods: The present, single-center, retrospective cohort study, conducted from January 2010 to April 2020, enrolled patients under age 2 years with moderate to severe upper airway obstruction who underwent an adenoidectomy or tonsillectomy. The patients were divided according to The Brodsky grading scale into group 1 (Grade 0 to 1 tonsils) or group 2 (Grade 2 or higher tonsils), who received only an adenoidectomy. Group 3 comprised patients with a concomitant adenoidectomy and tonsillectomy. Perioperative symptoms among the groups and the cumulative revision-free status and recurrence-free status rates in groups 1 and 2 were analyzed. Results: Fifty-three patients were enrolled. The median standard deviation score (SDS) for height and weight was −0.79 and −0.31, respectively. No postoperative complications, such as bleeding, were observed. However, two patients underwent intubation preoperatively due to severe obstruction. Seven patients underwent revision surgery. The cumulative revision-free and recurrence-free rates at week 60 were 81% and 100% for Group 1 and 42% and 48.5% for Group 2, respectively. The cumulative revision-free rate and cumulative recurrence-free rate were significantly higher in Group 1 (P < 0.0001; HR: 47.9; 95% CI: 1.12–2050 and P < 0.007; HR: 4.62; 95% CI: 1.37–15.6, respectively). None of the patients in Group 3 had revision surgery or symptom recurrence. Conclusion: Simple adenoidectomy in children with large tonsils carries a high risk of revision surgery. However, given the high risk of severe obstruction in very young children with OSDB, timely surgery is recommended. Level of Evidence:3.